The Relationship Between Employee Competencies And Employee Performance In A Government-Linked Company (GLC) - Eshwari Priya, Ravindra (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study is aimed at investigating the relationship between employee competencies and employee performance in a government-linked company (GLC). This research as done by using quantitative method where the data were collected by using questionnaires as the instrument. The questionnaires were in the form of Google Forms online due to the pandemic situation and the data was collected from 460 samples in one of the government-linked company in Bintulu, Sarawak. The data were then analysed by using both descriptive and inferential statistics. Besides, Pearson Correlation test procedure was used to measure the relationships between the independent variables and the dependent variables. The finding have shown that there is a significant relationship between the employee competencies and the employee performance. It was also found that …. is the most dominant factor affecting employee performance. As such, the researcher has recommended a focus on the study that may guide the organizations and future researches.